2016
DOI: 10.1248/yakushi.16-00081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Education for Diabetic Outpatients by a Hospital Pharmacist: A Retrospective Study

Abstract: The number of patients with diabetes continues to increase in Japan, which means that education in disease management is important. However, there have been few investigations into the importance of hospital pharmacists performing outpatient education for diabetes mellitus in Japan. In the diabetes outpatient department of Kitakyushu City Moji Hospital, a pharmacist commenced patient education using check sheets before patients saw the physicians from 2012. We divided the patients into groups with an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…The articles included for the analyses ranged from 2003 to 2019 and were conducted in 13 different countries. The majority of the studies were conducted in the USA (n. 15) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]; three in Iran [ 45 , 46 , 47 ] and Korea [ 8 , 48 , 49 ]; two in Canada [ 50 , 51 ] and the UK [ 52 , 53 ]; one in China [ 7 ], Belgium [ 6 ], Bulgaria [ 54 ], Hong Kong [ 55 ], Japan [ 56 ], Malaysia [ 57 ], Mexico [ 58 ], and Taiwan [ 59 ]. Considering articles’ design the majority (n. 21) was a Randomized Control Trial [ 7 , 8 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 45 , 47 , 48 , 49 , 51 , 52 , 53 , 57 ]; seven were a pre-post study [ ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles included for the analyses ranged from 2003 to 2019 and were conducted in 13 different countries. The majority of the studies were conducted in the USA (n. 15) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]; three in Iran [ 45 , 46 , 47 ] and Korea [ 8 , 48 , 49 ]; two in Canada [ 50 , 51 ] and the UK [ 52 , 53 ]; one in China [ 7 ], Belgium [ 6 ], Bulgaria [ 54 ], Hong Kong [ 55 ], Japan [ 56 ], Malaysia [ 57 ], Mexico [ 58 ], and Taiwan [ 59 ]. Considering articles’ design the majority (n. 21) was a Randomized Control Trial [ 7 , 8 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 45 , 47 , 48 , 49 , 51 , 52 , 53 , 57 ]; seven were a pre-post study [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen articles considered all these different types of outcomes together [ 6 , 30 , 31 , 32 , 34 , 38 , 40 , 44 , 49 , 50 , 52 , 54 , 57 , 59 ]; one article considered behavioral, psychological, and literacy outcomes [ 43 ]; one article considered clinical, behavioral, and psychological outcomes [ 49 ]; one article considered clinical, psychological, and literacy outcomes [ 41 ]; one article considered psychological and literacy outcomes [ 45 ]; one article considered behavioral and literacy outcomes [ 51 ]; six articles considered only clinical outcomes [ 33 , 35 , 39 , 48 , 56 , 58 ]; four articles considered only literacy [ 36 , 37 , 42 , 53 ]; and four articles considered only psychological outcomes [ 7 , 46 , 47 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been a serious increase in healthcare expenditures, 25) and it is therefore important that pharmacists develop an approach in consideration of the reduction of healthcare expenditures. It has been reported that the reduction of adopted medicines, 26) infection control and prevention, 27) and proper reuse of excess drugs 28) can contribute to the reduction of healthcare expenditures. Murata et al reported that the adjustment of antipsychotics in the psychiatric ward had an economic impact.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant association between the patient's better knowledge and the patient's longer duration of insulin therapy (≥1 year) ( P = .025) and receiving consultation from the health professionals ( P = .001). Several recent studies have shown the importance of hospital pharmacists performing patient education for diabetes mellitus 10,13,23 …”
Section: Discussionmentioning
confidence: 99%